Impact of Early Intervertebral Osseous Union After Posterior Lumbar Interbody Fusion on Health-Related Quality of Life. Issue 3 (April 2022) - Ushirozako, Hiroki; Hasegawa, Tomohiko; Ebata, Shigeto; Ohba, Tetsuro; Oba, Hiroki; Mukaiyama, Keijiro; Shimizu, Satoshi; Yamato, Yu; Ide, Koichiro; Shibata, Yosuke; Ojima, Toshiyuki; Takahashi, Jun; et al.
Study Design: Retrospective cohort study. Objectives: Nonunion after posterior lumbar interbody fusion (PLIF) is associated with poor improvements in health-related quality of life (HRQOL). We aimed to investigate the influence of early osseous union after PLIF on HRQOL. Methods: We reviewed 138 patients with 1-level PLIF (mean age 67 years, follow-up period ≥1 year). Postoperative lumbar computed tomography was performed to assess screw loosening and intervertebral union. HRQOL was assessed using the Japanese Orthopaedic Association Back Pain Evaluation Questionnaire. Results: Thirty-nine patients (28%) showed complete union at 6 months postoperatively (early union group). Twenty-eight patients (20%) showed complete union at 6 to 12 months postoperatively (delayed union group), while 71 patients demonstrated noncomplete union. Effective improvement of lumbar spine dysfunction and psychological disorders was achieved in 19 (63.3%) and 17 (50.0%) patients in the early union group, in 9 (42.9%) and 14 (53.8%) patients in the delayed union group, and in 22 (34.9%) and 19 (29.2%) patients in the nonunion group, respectively ( P = .036 and P = .036, respectively). The nonunion group had a significantly higher proportion of cases with screw loosening at 6 and 12 months postoperatively than the complete union group ( P = .033 and P = .022). Conclusions: Lumbar spine dysfunction and psychological disorders improved in cases with early complete union compared to those with nonunion. Screw loosening occurred in cases with nonunion predominantly from 6 months postoperatively. Therefore, the achievement of early complete union might be helpful for better HRQOL and lower incidence of postoperative complications.